2021
DOI: 10.1002/ajmg.a.62609
|View full text |Cite
|
Sign up to set email alerts
|

A novel variant in the dystonin gene causing hereditary sensory autonomic neuropathy type VI in a male infant: Case report and literature review

Abstract: The DST gene is located on chromosome 6p and encodes for a large protein. Alternative splicing of this protein produces the neuronal (a1-a3), muscular (b1-b3), and epithelial (e) isoforms. Hereditary sensory and autonomic neuropathy (HSAN) type VI is a rare autosomal recessive disorder due to mutations affecting the a2 isoform. We present a case of HSAN-VI in a male neonate born to consanguineous parents.Genome sequencing revealed a novel homozygous variant (DST_c.1118C > T; p.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
2
5
0
Order By: Relevance
“…Biallelic variants in the neuronal isoforms cause HSAN6 (MIM: 614653) which has been reported in several unrelated families with highly variable phenotypes (Table 1). 6–20 HSAN6 was initially described in a family of four affected individuals who presented with severe dysautonomic symptoms, distal contractures, severe psychomotor retardation, and early death 8 . The motor phenotype of the affected fetus reported here is similar to the affected individuals reported by Edvardson et al More recently, HSAN6 was reported as associated with congenital contractures 9,10 .…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…Biallelic variants in the neuronal isoforms cause HSAN6 (MIM: 614653) which has been reported in several unrelated families with highly variable phenotypes (Table 1). 6–20 HSAN6 was initially described in a family of four affected individuals who presented with severe dysautonomic symptoms, distal contractures, severe psychomotor retardation, and early death 8 . The motor phenotype of the affected fetus reported here is similar to the affected individuals reported by Edvardson et al More recently, HSAN6 was reported as associated with congenital contractures 9,10 .…”
Section: Discussionsupporting
confidence: 79%
“…HSAN6 was initially described in a family of four affected individuals who presented with severe dysautonomic symptoms, distal contractures, severe psychomotor retardation, and early death 8. The motor phenotype of the affected fetus reported here is similar to the affected individuals reported by Edvardson et al More recently, HSAN6 was reported as associated with congenital contractures 9,10. The positions of DST variants in the cases associated with congenital contractures are not restricted to a specific domain of the DST protein (tion.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…79 DST-related HSAN6 is rare but has a severe presentation early in life with neonatal hypotonia, respiratory failure, areflexia, and dysautonomia. 80 HEREDITARY NEURALGIC AMYOTROPHY Hereditary neuralgic amyotrophy, also known as hereditary brachial plexus neuropathy or hereditary brachial neuritis, is an autosomal dominant disorder that typically presents with a recurrent painful brachial plexus neuropathy. Individual episodes are clinically and electrophysiologically indistinguishable from the common idiopathic neuralgic amyotrophy or Parsonage-Turner syndrome.…”
Section: Key Pointsmentioning
confidence: 99%
“…HSAN4 is also uniquely associated with variable degrees of intellectual disability and anhidrosis, which can be complicated by life-threatening hyperthermia 79 . DST -related HSAN6 is rare but has a severe presentation early in life with neonatal hypotonia, respiratory failure, areflexia, and dysautonomia 80 …”
Section: Hereditary Sensory and Autonomic Neuropathymentioning
confidence: 99%